2004
DOI: 10.1007/978-3-540-30202-5_48
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Mediation: A Procedure for the Cooperative Construction of Domain Ontologies

Abstract: Abstract. In order to enable knowledge sharing and reuse among software entities, artificial intelligence researchers have proposed to develop 'ontologies' as the explicit formal specifications of conceptualizations. These ontologies were normally designed by knowledge engineers who laid down the basic categories and relations for a certain domain. However, in any practical setting there will be conflicting interests which pertain to different conceptualizations of which a knowledge engineer will usually not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…of a domain) has not been recognised at all, although some research has addressed the collaborative dimension of ontology building (see Staab et al 2001, Sure 2002, Go´mez-Gauchı´a et al 2004a, 2004b, Pinto et al 2004, de Moor et al 2006; for a complete account of those approaches). From these, the ''Knowledge Mediation Procedure'' (Aschoff 2004), Application Knowledge Engineering Methodology (AKEM) (Zhao 2005) and Human-Centered Ontology Engineering Methodology (HCOME) (Kotis and Vouros 2006) are the works that address the collaboration dimension as fundamental and develop methods and techniques that can result in some form of shared conceptualisation. Nevertheless, from this literature review, it can be concluded that the importance of supporting the collective construction of a conceptualisation is not recognised.…”
Section: Generic Ontology Development Methods With Collaboration Compmentioning
confidence: 99%
“…of a domain) has not been recognised at all, although some research has addressed the collaborative dimension of ontology building (see Staab et al 2001, Sure 2002, Go´mez-Gauchı´a et al 2004a, 2004b, Pinto et al 2004, de Moor et al 2006; for a complete account of those approaches). From these, the ''Knowledge Mediation Procedure'' (Aschoff 2004), Application Knowledge Engineering Methodology (AKEM) (Zhao 2005) and Human-Centered Ontology Engineering Methodology (HCOME) (Kotis and Vouros 2006) are the works that address the collaboration dimension as fundamental and develop methods and techniques that can result in some form of shared conceptualisation. Nevertheless, from this literature review, it can be concluded that the importance of supporting the collective construction of a conceptualisation is not recognised.…”
Section: Generic Ontology Development Methods With Collaboration Compmentioning
confidence: 99%
“…[9]) and the cooperative construction of domain ontologies (e.g. [1]). Still, although these approaches work out basic principles for cooperative ontology engineering, they do not provide community-grounded methodologies addressing the issues of relevance and efficiency of definition processes.…”
Section: Interorganizational Ontology Engineeringmentioning
confidence: 99%
“…However, they do not present any experiences or adaptations to the IBIS model for OE. This is the focus of the work described in [11]. A three-phased knowledge mediation procedure is proposed and evaluated.…”
Section: Ontology Engineeringmentioning
confidence: 99%